GRADUATES NEED TO UPHOLD INTEGRITY AND ACCOUNTABILITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 28 October 2016 Graduates who have achieved success in their institutions should continue to excel and uphold integrity and accountability, the trust and responsibility put upon them.